2012
DOI: 10.1139/h2012-077
|View full text |Cite
|
Sign up to set email alerts
|

Postexercise cooling interventions and the effects on exercise-induced heat stress in a temperate environment

Abstract: The aim of this study was to examine the effects of cool water immersion (20 °C; CWI) while wearing a cooling jacket (Cryovest;V) and a passive control (PAS) as recovery methods on physiological and thermoregulatory responses between 2 exercise bouts in temperate conditions. Nine well-trained male cyclists performed 2 successive bouts of 45 min of endurance cycling exercise in a temperate environment (20 °C) separated by 25 min of the respective recovery interventions. Capillary blood samples were obtained to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 61 publications
2
19
1
Order By: Relevance
“…The present study has confirmed the results obtained by Mokayef et al (2014), who demonstrated the high efficiency of CWI not only with regard to passive rest, but also active rest (slow running with 40-60% of VO 2max ). The similar efficiency of CWI in accelerating lactate clearance was also shown by Hausswirth et al (2012). On one hand, these findings support the effectiveness of CWI in post-exercise recovery as suggested in the literature (Pournot et al, 2011;Pointon et al, 2012), but on the other, they show that the impact of IM has still been poorly documented.…”
Section: Lactate Removalsupporting
confidence: 86%
See 1 more Smart Citation
“…The present study has confirmed the results obtained by Mokayef et al (2014), who demonstrated the high efficiency of CWI not only with regard to passive rest, but also active rest (slow running with 40-60% of VO 2max ). The similar efficiency of CWI in accelerating lactate clearance was also shown by Hausswirth et al (2012). On one hand, these findings support the effectiveness of CWI in post-exercise recovery as suggested in the literature (Pournot et al, 2011;Pointon et al, 2012), but on the other, they show that the impact of IM has still been poorly documented.…”
Section: Lactate Removalsupporting
confidence: 86%
“…The basic effects of cold treatments include the reduction of inflammatory processes, pain relief, and the counteraction of DOMS symptoms (Hausswirth et al, 2012;Ziemann et al, 2012;Ne´de´lec et al, 2013). In accordance with the recommendations, the skin temperature has to be lowered by 5-15°C to obtain the analgesic effect (Bailey et al, 2007;Bleakley and Davidson, 2010).…”
Section: Ir and Domsmentioning
confidence: 99%
“…For instance, cycling time trials in thermoneutral conditions have been shown to increase core temperature (T c ) 1-2 °C depending on exercise intensity (Nybo et al, 2001;Drust et al, 2005;Périard et al, 2011;Hausswirth et al, 2012); this results in elevated skin blood flow (Périard et al, 2011). The increased T c with a concomitant increase in skin blood flow exacerbates cardiovascular strain via reduced central venous pressure and subsequent reduced stroke volume and increased HR, all of which can impair performance (Roberts & Wenger, 1979).…”
Section: Impact Of Heat Stress On Exercise Performancementioning
confidence: 99%
“…Thermoneutral conditions are considered compensable in that heat dissipation mechanisms enable maintenance of thermal homeostasis (Nybo et al, 2001;Drust et al, 2005;Périard et al, 2011;Hausswirth et al, 2012). Generally, performance impairments under such conditions are thereby the result of issues unrelated to thermoregulation, such as failure of central and peripheral neural drive, diminished response of muscles to neural stimulation (e.g., action potentials), and/or impaired excitation-contraction coupling-related mechanisms (Abbiss & Laursen, 2005).…”
Section: Physiological Factors Limiting Exercise In the Heatmentioning
confidence: 99%
See 1 more Smart Citation